More than meets the eye: Toward a reassessment of Old English double accusatives - Vázquez González, Juan G. (ExELL, 2025)
This article offers a corpus-based update of the Accusative-Accusative construction as part of a much-needed reanalysis of Old English double-object complementation. Unlike the better-known Dative-Accusative pattern—the basis for the Modern English ditransitive — double accusatives remain largely ignored because of their extremely low productivity. Using the Dictionary of Old English Corpus, this study extends the body of evidence to a total of 30 verb types and 87 tokens, providing better precision. Apart from relating to speech act verbs and metaphorical transfer, double accusatives are now found operating as theme-recipients, beneficiaries, and, less frequently, as theme-goals or maleficiaries. This investigation proves their continuity through early and late Old English, attestation across many varieties and text types, and use in Latin-to-English morphosyntactic translation.